2022
DOI: 10.1037/dev0001419
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of gender identity and preferences across time: An exploration among cisgender and transgender children.

Abstract: While considerable research has examined gender development in middle childhood, little longitudinal work has been conducted at this time to indicate whether, for example, youth who show more or less gender conformity at one point continue to do so later. The present study investigated the consistency of gender identity and preferences for gender-stereotypical toys, clothing, and same-gender peer preferences among groups of transgender youth (n = 158), their siblings (n = 79), and an unrelated group of cisgend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Diverse samples should also include the presence of non-cisgender and sexually diverse individuals, as the current study only included heterosexual, cis-gender emerging adults. Previous work supports that gender development is comparable between cisgender individuals and transgendered persons when their gender is affirmed (Hässler et al, 2022), suggesting our work could be paralleled with transgendered persons. Given society's emphasis on heteronormativity, however, future work should investigate how sexist attitudes that are entrenched in patriarchal ideals impact LGBTQ+ emerging adults.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…Diverse samples should also include the presence of non-cisgender and sexually diverse individuals, as the current study only included heterosexual, cis-gender emerging adults. Previous work supports that gender development is comparable between cisgender individuals and transgendered persons when their gender is affirmed (Hässler et al, 2022), suggesting our work could be paralleled with transgendered persons. Given society's emphasis on heteronormativity, however, future work should investigate how sexist attitudes that are entrenched in patriarchal ideals impact LGBTQ+ emerging adults.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…Even longitudinal studies typically ask participants about their gender identity only once, overlooking ways that understanding of gender identity may vary or change for youths over time. Although a few longitudinal studies 13 , 14 have examined whether gender identity varies among socially transitioned TGD children, trajectories of gender identity in samples of youths are still not well understood. 47 , 48 In this community-based longitudinal cohort study, 1 in 5 (18.3%) youths reported a different gender identity over a period of approximately 3.5 years (the majority reported the same gender identity over time).…”
Section: Discussionmentioning
confidence: 99%
“…However, interpretation from these studies are limited because a substantial proportion of study participants were subthreshold for GID diagnosis in childhood, 11 and using such outdated diagnostic criteria is problematic because one could meet GID in childhood criteria without necessarily identifying as TGD. 12 Nonetheless, recent work 13 , 14 indicates that a large majority of socially transitioned TGD children still identified as TGD 2.5 to 5 years later. Similarly, a UK study 15 found that among TGD youths, 91.7% continuously identified as TGD while being followed up by a gender clinic for minors.…”
Section: Introductionmentioning
confidence: 99%
“…The toys and outfits varied in degree of gender‐typing and were arranged on a 5‐point scale to represent very feminine, slightly feminine, gender‐neutral, slightly masculine, and very masculine items. These stimuli have been used in several prior examinations of preschool‐aged children (e.g., Gülgöz et al, 2019; Hässler et al, 2022; Rae et al, 2019), and the toys were selected based on objects in prior studies found to elicit gender‐typed preferences in children (e.g., transportation toys, construction toys, dolls, kitchen supplies) as well as those considered gender neutral (board games and jigsaw puzzles; Halim et al, 2014; see also Davis & Hines, 2020). The stimuli were also designed to ensure that the various facets that children use to ascribe a gender label to an object were visible (e.g., function, themes, colors; Cherney, 2018).…”
Section: Methodsmentioning
confidence: 99%